EVALUATION OF GOVERNMENT EXPENDITURE PLANNING METHODS - Žubule, Ērika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The topicality of the research problem is justified by the fact that each country's sustainable development is affected by the government's policies. One of its main components is a fiscal or budgetary policy. Traditionally, it is defined as the money required for making a revenue and expenditure policy that is needed to ensure the government’s functioning, but the economic interpretation says it is the economy regulation system through taxes and government spending.In the finance theory and practice, great attention is paid to the part of expenses, saying that the most efficient budget reforms are possible in the area of government expenses. It is emphasized that the diminishing of state expenses is possible already in the process of budget planning by increasing the reliability of users of budget funds. The state`s finance practice offers several models reflecting problems in the sphere of planning budget expenses. The aim of the research – to evaluate methods of planning government budget expenses used in the state`s finance practice and identify the figures of their efficiency, their problems and suggesting possible solutions.